Seawater Masses Characteristics of The Bali Sea Based on CTD Yo-Yo Casting - Gentio Harsono; Budi Purwanto; Rudy A.G. Gultom; Tunggul Puliwarna; Johar Setiyadi; Kentaro Ando; Mario Cobral (Ilmu Kelautan)
The Bali Sea is located between the Java Sea and the Lombok Strait, which is one of the Indonesian Through Flow  exits, especially the western route. These waters are possible to be the meeting place and mixing of two water masses with significantly different characteristics, that is the watermass brings by Indonesian Through Flow and Indian Ocean watermass. This study describes the watermasses and its turbulent mixture in the Bali Sea using CTD Yo-Yo casting data and spatial monsoonal wind distribution. The vertical distribution of energy dissipation rate and diapycnal diffusivity in the Bali Sea was computed based on measurement data during KRI RIGEL 933 expedition on April, 2021. KRI RIGEL is operated by Hidro-Oceanographyc Center Indonesian Navy’s. Identified 4 types of water masses in a row, there are Java Sea water masses, mixed water masses between Java Sea and ITF, NPSW and NPIW with modified water mass property characters. The internal tides formed in the sills of the Lombok Strait are thought to contribute to the turbulent mixing parameters in the Bali Sea. The values obtained for energy dissipation and diapycnal diffusivity are 1.58 x 10-9 W Kg-1 and 5.07 x 10-5 m2 s-1, respectively. The value of this turbulent mixing parameter is confirmed to be smaller than the mixing value in the Lombok strait and is equivalent to the open sea. It is seen that there is a transformation of water mass which is marked by a shift in the density value in the identified water mass type.